Assessment of Fasciola and Paramphistomes co-infection in large ruminants through faecal egg counts around Taiping, Malaysia - N., Che-Kamaruddin; Isa, N. M. M. (Malaysian Society of Parasitology and Tropical Medicine, 2023)
Emerging cases of Fasciola and Paramphistomes co-infection have been reported, especially in tropical regions. This is due to Fasciola and Paramphistomes sharing biological factors which influence the pattern of transmission, especially in faecal egg shedding due to interaction and competition in the definitive host. Most reports surveyed the occurrence of fasciolosis in ruminants with a lack of observation of faecal egg distribution. Therefore, present study is aimed to assess the distribution of Fasciola and Paramphistomes faecal egg count (fec) in co-infected large ruminants in Larut, Matang, and Selama areas (Taiping). A total of 371 faecal samples were collected at random from 23 ruminant herds. Flukefinder® sedimentation was used to quantify the Fasciola and Paramphistomes eggs. Descriptive analyses were performed to determine the prevalence of co-infections, and Spearman correlation analysis was used to correlate the fec. Overall, the prevalence of Fasciola and Paramphistomes co-infection was 23.7% (n=89/371) in Taiping. Prevalence of paramphistomosis was always higher than fasciolosis in overall and single infection, with 46.9% (n=174/371) and 22.9% (n=85/371) compared to 36.9% (n=137/371) and 12.9% (n=48/371) respectively. Egg per gram (epg) of both parasites were positively skewed with a median of 1.5 epg in fasciolosis and 10.5 epg in paramphistomosis. Spearman correlation analysis of the epg in co-infected bovine was found to have a moderately positive correlation with rs=0.39 (p-value<0.01). The recent study observed a moderate prevalence of Fasciola and Paramphistomes coinfection in a large ruminant population from Taiping, with the prevalence of paramphistomosis being higher than fasciolosis. Hence, this suggests that infection with one of these parasites increases the chance of infection with another. There is a need to integrate fec in parasite surveillance to monitor the trend of parasite transmission. Findings in the present study could tailor control strategies, especially for fasciolosis to limit the economic loss and prevent zoonotic transmission.